PENGELOLAAN SAMPAH MELALUI PEMILAHAN DAN PEMANFAATAN SAMPAH PLASTIK SERTA KULIT BUAH SEBAGAI BAHAN ECO-ENZYME - Syifa Fauziah Yasid; Joko Pramono; Rafika Rahmawati (An-Nizam, 2022)
The problem of waste is familiar to hear, especially household waste. This can be seen in one of the villages in Karawang Regency, named Kutamukti Village, especially in Poris Village. Poris Village is the second village with the highest population. Surely this results in a lot of waste that will be generated from daily activities including household activities. Waste Management in Poris Village is still very worrying because the majority of people still dispose of household waste in the river or burned. This is due to the lack of public understanding of the management and utilization of household waste. By providing socialization, practice, and counseling related to waste management and utilization, the community will understand and realize that waste greatly affects the health of the environment and the health of the people around it. The existence of these activities, the community will be able to manage household waste by sorting waste 3R (Reduce, Reuse, and Recycle) and use it to plant from plastic bottles and as a material for making eco-enzyme. That way will make the surrounding environment clean, comfortable, and the quality of the environment is maintained.